Analisis Ekonomi Usahatani Jagung di Kabupaten Blora (Biaya dan Pendapatan) - Ibnu Nafik; Joko Sutrisno; Indah Nurhidayati (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
With a large percentage of its population working in agriculture, Indonesia is an agrarian country. Currently, Indonesia has not achieved maize self-sufficiency. The substantial increase in maize imports reflects Indonesia's growing dependence on foreign supplies. Indonesia imports maize from countries such as the United States, Thailand, South Africa, Brazil, and Argentina. Blora District is the second-largest maize harvest area in Central Java Province. In the last three years, maize production in the Blora district has increased, indicating the potential to increase maize production further. This study analyzes the costs, revenues, and income of maize farming in the Blora district. The primary method used in this research is descriptive quantitative analysis. This research was conducted in April-June 2024. The research location was purposively selected in the Blora district, particularly in Todanan, Randublatung, and Jati sub-districts. The research variables used in this study were maize production (kg), land area (Ha), labor (HOK), seeds (kg), urea fertilizer (kg), phonska fertilizer (kg), other fertilizers (kg), and pesticides (liters). Based on Lemeshow's formula, the sample obtained in this study was 92.1984, then researchers simplified it to 92 farmer samples. The distribution of the number of farmer samples in the Blora district was 32 samples for the Randublatung sub-district, 30 samples for the Todanan sub-district, and 30 samples for the Jati sub-district. The analysis method used was cost, revenue, and farm income analysis. The study concluded that maize production in the Blora district requires an average farming cost of IDR 6,164,101.06 for one planting season per 0.44 hectare. The average revenue generated from maize production per 0.44 hectare is IDR 17,573,500. The average income farmers earn from maize farming in Blora district is IDR 11,409,268.50 per 0.44 hectare.